Neuroprotective Effects of 17β-Estradiol Rely on Estrogen Receptor Membrane Initiated Signals - Fiocchetti, Marco; Ascenzi, Paolo; Marino, Maria (Frontiers in Physiology, 2012)
17β-estradiol (E2) exerts protective effects in the central nervous system besides its crucial role in many physiological and pathological events. E2 effects are not restricted to the brain areas related with the control of the reproductive function, but rather are widespread throughout the developing and the adult brain. E2 actions are mediated by estrogen receptors (i.e., ERα and ERβ) belonging to the nuclear receptor super family. As members of the ligand-regulated transcription factor family, the actions of ERs in the brain were thought to mediate only the E2 long-term transcriptional effects. However, a growing body of evidence has emerged indicating the presence of rapid, membrane initiated E2 effects in the brain which result independent from ER transcriptional activities and involved in E2-induced neuroprotection. Aim of this review is to focus on the rapid effects of E2 in the brain taking into account the specific contribution of the signaling pathway of ERβ subtype in neuroprotective actions of E2.